2019
DOI: 10.3757/jser.78.581
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Vestibular Rehabilitation on Improving the Gait in patients with Chronic Unilateral Vestibular Disorder

Abstract: There are few reports in Japan of investigation of the effect of vestibular rehabilitation (VR) by physical therapists (PT). This study was aimed at examining the effectiveness of vestibular rehabilitation therapy (VRT) for patients with unilateral peripheral vestibular disorder. The subjects were nine patients with chronic unilateral peripheral vestibular disorder. PTs provided VR, consisting of eye movement exercises, body balance exercises, walking exercises, daily activity movement exercises, to the subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Providing supervision and customizing of home exercises in short intervals have been shown to improve walking ability and postural control. We previously found that 3 months of continued training was required to induce a significant improvement in vestibular function and home exercises when interventions were provided once a month 27) . Training may exhibit immediate results if patients continue to receive instructions at appropriate intervals and in a manner suitable to their individual abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Providing supervision and customizing of home exercises in short intervals have been shown to improve walking ability and postural control. We previously found that 3 months of continued training was required to induce a significant improvement in vestibular function and home exercises when interventions were provided once a month 27) . Training may exhibit immediate results if patients continue to receive instructions at appropriate intervals and in a manner suitable to their individual abilities.…”
Section: Discussionmentioning
confidence: 99%